Impact of Giant Sea Wall Construction on Surrounding Current Patterns and Abrasion Rates: A Numerical Hydrodynamic Simulation of Marine Dynamics - Darius Arkwright; Andre Kusuma Putra (Structures, Infrastructure, Planning, Implementation, and Legislation, 2026)
The increasing trend of global sea level rise and localized land subsidence in Jakarta Bay has led to the consideration of large-scale coastal protection measures, yet the hydrodynamic consequences of such infrastructure remain insufficiently quantified. This study evaluates the impact of the Giant Sea Wall (GSW) on local current patterns and coastal morphology using a validated three-dimensional numerical simulation. The study focuses on a 25 × 30 km domain in Jakarta Bay, integrating high-resolution bathymetric data (BATNAS), wind time series from BMKG, and tidal harmonic components from BIG. A finite volume scheme on an unstructured mesh is applied to solve the shallow water equations, with validation showing a correlation coefficient of 0.92 against observed tidal data from Pushidrosal. Simulation results suggest that current velocities may increase to approximately 0.62 m/s near structural termini, potentially inducing localized scouring and increased abrasion rates in down-drift areas, with a projected shoreline recession of approximately 3.5 m/year under modeled conditions. These findings indicate that while the GSW can reduce tidal flooding in protected urban areas, it may also redistribute hydrodynamic energy toward adjacent coastal zones, increasing erosion risks. Adaptive strategies, including sediment nourishment and permeable structural designs, should therefore be considered. Future research is recommended to incorporate fully coupled morphodynamic models to improve long-term projections.